The Development of Research-Based Learning Materials with Problem Solving and Problem Posing Oriented of Mathematics Statistics - Krisdiana, Ika; Masfingatin, Titin; Murtafiah, Wasilatul (Universitas Islam Raden Intan Lampung, INDONESIA, 2018)
This study aims to describe the feasibility of research-based learning materials with problem solving and problem posing oriented of Mathematics Statistics. This research is a development research refers to the instructional development cycle by Fenrich (1997). Data collection techniques by observation, tests, and closed questionnaires. Data analysis techniques used qualitative and quantitative descriptive analysis (mixing method). The results: (1) a valid Semester Learning Plan (RPS) both in content and construct, Student Activity Sheet (LKM) based on research and a Learning Result Test (THB) assessment sheet with good and very good assessment from the validator that can be used with few revision, (2) positive response from students to teaching materials amounted to 88.67%, (3) effectiveness of teaching materials was seen based on student learning completeness of 78.20%and better compared to classes that are not taught to use research-based learning teaching materials developed. The development of research-based learning materials with problem solving and problem posing oriented are valid, practic and effective that suitable for use in Statistics Mathematics learning process.